The Role of Attention to Emotion in Recovery from Major Depressive Disorder. (18th June 2013) - Thompson, Renee J.; Mata, Jutta; Jaeggi, Susanne M.; Buschkuehl, Martin; Jonides, John; Gotlib, Ian H.
Abstract : Major Depressive Disorder (MDD) is characterized by several emotional disturbances. One possible but not well-examined disturbance is in attention to emotion, an important facet of emotional awareness. We examined whether attention to emotion predicted recovery from MDD. Fifty-three adults with current MDD completed a week of experience sampling (Time 1). At each prompt, participants reported attention to emotion, negative affect (NA), and positive affect (PA). Approximately one year later (Time 2), the depressive status of 27 participants was reassessed. Participants who had recovered from MDD (n = 8 ) indicated paying less attention to their emotions at Time 1 than did participants who had not fully recovered (n = 19 ). Attention to emotion was better predictor of recovery than was severity of MDD, NA, or PA at Time 1. Levels of attention to emotion at Time 1 in participants who recovered from MDD did not differ significantly from the levels reported by 53 never-depressed individuals who had participated in the experience sampling. Findings indicate that high levels of an otherwise adaptive emotional facet can adversely affect the course of MDD.